PERBANDINGAN KANDUNGAN GIZI GULAI KAMBING MENGGUNAKAN SANTAN DAN SUSU BUBUK SKIM - Putu Eka Trisdayanti; I Made Ade Kusuma Putra (JURNAL GASTRONOMI INDONESIA, 2021)
Curries that use coconut milk are high in calories and can also cause high cholesterol, coconut milk can also make food spoil quickly. It is important to have an alternative to coconut milk used for cooking curry, such as powdered milk. The use of powdered milk as a substitute for coconut milk has been done before, with the result that goat curry using powdered milk was acceptable. In this study, researchers tested the comparison of the nutritional content of goat curry using coconut milk and goat curry using skim milk powder. Data collection was carried out by experiment and laboratory tests (nutrition). The results of this study showed that goat curry using coconut milk had a higher calorie, protein, and fat content, while the carbohydrate content is lower than that of goat curry using skim milk powder